Dynamic Evolution of the Glymphatic System at the Early Stages of Subarachnoid Hemorrhage - Hou, Changkai; Li, Jian; Wang, Bangyue; Liu, Quanlei; Zhao, Yan; Zhang, Hao; Wang, Weihan; Ren, Wen; Cui, Xiaopeng; Yang, Xinyu (Frontiers in Neurology, 2022)
The early stages of subarachnoid hemorrhage(SAH) are extremely important for the progression and prognosis of this disease. The glymphatic system (GS) has positive implications for the nervous system due to its ability to clearance tau and amyloid-β (Aβ) protein. Previous studies have shown that GS dysfunction will appears after SAH. However, there is no systematic evaluation of the degree of damage and development process of GS function in the early stage after SAH. In this study, we evaluated the GS function and neurobehavioral in the sham, 6h, 1D, 3D and 7d after SAH, respectively. Our results showed that the function of GS was severely attenuated in mice after SAH, with decreased polarity of Aquaporin-4(AQP4), increased expression of AQP4 and a linear correlation with the Dystrophin-Associated complex(DAC), proliferation of reactive astrocytes, increased tau protein accumulation, and decreased neurological function. Collectively, these findings provide a comprehensive understanding of the functional changes of GS after SAH, provide references for subsequent scholars studying SAH, and suggest some potential mechanistic insight that affect AQP4 polarity and GS function.